Paris and the birth of the modern fantastic during the Nineteenth century - García, Patricia (2017)
In her article "Paris and the Birth of the Modern Fantastic during the Nineteenth Century" Patricia Garcia discusses the unprecedented growth of Europe's urban centers during the nineteenth century in relation to the realist novel and takes urban and literary Paris as a paradigm. However, nineteenth-century Paris was also to become the epicenter of another narrative form: the fantastic. Garcia's objective is to explore how the modern city fueled the development of the fantastic by combining the literary and urban angle: how do works of the fantastic write the city? What role does the modern city play in the emergence of the fantastic short story? Her argumentation is divided into two parts: the first explores how literature circulated in space while the second focuses on the representations of Paris in nineteenth-century fantastic fiction to demonstrate that with the acceleration of modernity, the fantastic became an urban form of expression.